Modeling and Experimental Study on Dynamic Characteristics of Dual-Mass Flywheel Torsional Damper - Long Chen; Wen-ku Shi; Zhi-yong Chen (Shock and Vibration)
Theoretical modeling and experimental research are carried out on the dynamic torsional characteristics of a dual-mass flywheel (DMF) in this paper. Firstly, the structure and working principle of the DMF are analyzed. Secondly, the arc spring is analyzed by the discrete element method. For the different frictional torques in the working process, the linear fitting and equivalent energy methods are used to model the frictional torque under the dynamic condition of the arc spring. The fractional derivative model is used to model the viscous damping of DMF. Then, the parameter identification and model verification are carried out on the model, and the model error is analyzed. Finally, an experimental study on the dynamic torsional characteristics of DMF is carried out. The results demonstrate that the torsional stiffness of the DMF varies with the excitation amplitude and frequency. This modeling and test method can be used for structural design and performance prediction analysis of DMF.